Photography by Massinissa Garaoun | Linguistic fieldwork in North Africa | Snowy mountains of the Babors during spring - (:unkn) unknown (My University, 2023)
This photograph has been captured by Massinissa Garaoun, in the Snowy mountains of the Babors during spring taken from the threshold of the mausoleum of Imma Tadrart (Tabellout, commune of Aokas).This was part of a linguistic survey to document Tasahlit [θasaħliθ], a Berber language spoken by approximately 200 000 speakers in the western third of the Babor Range in Eastern Kabylia (Algeria).
Keywords: African Research